2009
DOI: 10.1111/j.1432-2277.2009.00864.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful hepatitis B vaccination in liver transplant recipients with donor-specific hyporesponsiveness

Abstract: Summary Currently, patients are prescribed lifelong treatment with hepatitis B immunoglobulin (HBIg) after liver transplantation (LT) for hepatitis B virus (HBV)‐related diseases in order to prevent reinfection with HBV. Active immunization with an HBV vaccine would be a preferable alternative; however, the immunosuppressive environment in LT recipients is believed to elicit a poor response to vaccination. Minimizing the exposure of the HBV‐infected LT recipients to immunosuppressants would be beneficial in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…There is no direct evidence to confirm this speculation, so further investigation will be necessary. In one recent report by Tahara et al [29], relatively good HBV vaccine response was shown even in HBV chronic carrier cases. They monitored patients' immune status by a mixed lymphocyte reaction assay using carboxyfluorescein (CFSE), and showed that vaccine responses were correlated to the level where only immune response of antidonor lymphocyte was suppressed and that of anti-third party lymphocyte was maintained, irrespective of trough levels of calcineurin inhibitors.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…There is no direct evidence to confirm this speculation, so further investigation will be necessary. In one recent report by Tahara et al [29], relatively good HBV vaccine response was shown even in HBV chronic carrier cases. They monitored patients' immune status by a mixed lymphocyte reaction assay using carboxyfluorescein (CFSE), and showed that vaccine responses were correlated to the level where only immune response of antidonor lymphocyte was suppressed and that of anti-third party lymphocyte was maintained, irrespective of trough levels of calcineurin inhibitors.…”
Section: Discussionmentioning
confidence: 97%
“…HBsAb [100 IU/l without HBIg administration for more than 3 months was judged to indicate success of this vaccine protocol according to the previous reports for HBV prophylaxis [11,26,27] and vaccine effect [28,29]. If this level could be attained, lamivudine treatment could be stopped.…”
Section: Study Protocolmentioning
confidence: 99%
“…By assessing a recipient's immunosuppressive status with the precise manner, Tahara et al [14] reported good results of vaccination, giving a 64.7% response rate. They assessed the recipient's immunosuppressive status using donor lymphocyte and the third-party lymphocyte, and by keeping the anti-donor-specific immunosuppression, they adjusted the dose of immunosuppressive agents.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, this indicator has been widely used not only in LT, but also in various organ transplantations. In our institution, the ImmuKnow assay has been introduced for LDLT recipients since 2011 [14,15]. By using this assay, LDLT recipients are categorized into the three established zones of immune response: low response, moderate response, and strong response.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] Active immunization with standard hepatitis B vaccines in these patients is considered a promising substitute to the current treatment strategy, although the results of this new strategy have been controversial. [12][13][14][15][16][17][18][19][20][21][22] Some studies have reported that responders to hepatitis B vaccination, defined as patients with anti-HBs, should stop taking HBIG and/or antiviral agents. 12,16,17,[20][21][22] However, the safety of discontinuing HBIG and/or antiviral agents in responders remains unclear.…”
Section: Introductionmentioning
confidence: 99%